2010
DOI: 10.3109/02713681003760150
|View full text |Cite
|
Sign up to set email alerts
|

Structural Collagen Alterations in Macular Corneal Dystrophy Occur Mainly in the Posterior Stroma

Abstract: Collagen fibril spacing is reduced and large-diameter collagen fibrils are seen in macular corneal dystrophy type I, with the deep stroma affected more. We speculate that the ultrastructural abnormalities are more prevalent in the posterior stroma because the structural influence of sulphated keratan sulphate glycosaminoglycans/proteoglycans is high in this region of the cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
9
1
Order By: Relevance
“…Intra‐ and extracellular accumulation of glycosaminoglycans in the stroma, Descemet's membrane, and endothelium is seen on histopathology. Collagen fibril spacing is reduced and large‐diameter collagen fibrils are seen, with the deep stroma being more severely affected . The corneal sensitivity was not evaluated in the described patients and photophobia was not described, although one patient was reported to show recurrent epiphora.…”
Section: Discussionmentioning
confidence: 99%
“…Intra‐ and extracellular accumulation of glycosaminoglycans in the stroma, Descemet's membrane, and endothelium is seen on histopathology. Collagen fibril spacing is reduced and large‐diameter collagen fibrils are seen, with the deep stroma being more severely affected . The corneal sensitivity was not evaluated in the described patients and photophobia was not described, although one patient was reported to show recurrent epiphora.…”
Section: Discussionmentioning
confidence: 99%
“… 9 This is thought to arise from a reduction in water-binding potential in the extrafibrillar space, alluded to above, augmented by a lack of mutual repulsion between charged KS side chains on KS-PGs, whose protein cores are bound to collagen fibrils. Indeed, this concept finds some support in depth-profiled studies of collagen fibril spacing in human MCD corneas, which show that the compaction of collagen fibrils is more prevalent in the posterior corneal stroma, 9 , 44 a region of the tissue in mammalian corneas in which KS-GAGs are most abundant. 45 47 Reduction in center-to-center distance between collagen fibrils was observed in x-ray diffraction studies of Chst5 -null corneal tissue, 14 further demonstrating a role for KS-PGs in maintenance of interfibrillar spacing.…”
Section: Discussionmentioning
confidence: 91%
“…For example, posterior stromal regions were found to be more severely affected by the disruption of fibril structure and organisation in decorin/biglycan compound mutant mice, suggesting a synergy of regulatory roles for proteoglycans, in this case decorin and biglycan, in matrix assembly (Zhang et al, 2009). As mentioned earlier, the deep stroma is also the most affected corneal region in macular corneal dystrophy, and this is where pockets of abnormally large diameter collagen fibrils are found (Palka et al, 2010). A subsequent study of the peripheral cornea in mice further showed that fibromodulin may cooperate with lumican in fibril regulation during postnatal corneal development (Chen et al, 2010).…”
Section: Electron Microscopymentioning
confidence: 92%
“…Recent SAXS studies of this disease have indicated that the major reduction in collagen fibril spacing occurs in the deeper stromal layers (Palka et al, 2010), which is possibly reflective of the proposed greater importance of keratan sulphate proteoglycans in the posterior stroma of the corneas of larger animals based on its preferential synthesis owing to a restricted oxygen supply (Scott and Haigh, 1988). WAXS experiments have also been conducted on post-operative macular dystrophy corneas and have consistently documented an unusual signal, corresponding to a periodic structure of 0.46 nm, which is not seen in x-ray patterns obtained from normal human corneas (Quantock et al, 1992; 1993a; 1997a).…”
Section: X-ray Scatteringmentioning
confidence: 99%